Analysis of immunotherapeutic response-related signatures in esophageal squamous-cell carcinoma - Zheng, Bohao; Li, Jie; Zhang, Mengdi; Zhang, Pengju; Deng, Weiwei; Pu, Yang (Frontiers in Immunology, 2023)
Background: Esophageal squamous cell carcinoma (ESCC) is one of the most common and lethal malignant diseases. Immunotherapy has been widely studied and has exhibited potential in ESCC treatment. However, there are only a portion of ESCC patients have benefited from immunotherapy. We herein identified immunotherapeutic response-related signatures (IRRS) and evaluated their performance in ESCC prognosis and immunotherapeutic responsiveness. Methods: We constructed an IRRS using the gene expression data of 274 ESCC patients based on significantly differentially expressed genes, which were compared responders and non-responders from various patient cohorts treated with immunotherapy. Survival analysis was performed in both the GSE53625 and TCGA-ESCC cohorts. We also explored the differences in the tumor microenvironment between the high-IRRS and low-IRRS score groups using single-cell data as a reference. Two immunotherapy cohorts were used to verify the value of the IRRS in predicting immunotherapy response. Results: Twelve immunotherapy-related genes were selected to construct a signature score and were validated as independent prognostic predictors for patients with ESCC. Patients with high IRRS scores exhibited an immunosuppressive phenotype. Therefore, patients with low IRRS scores may benefit from immunotherapy. Conclusions: IRRS score is a biomarker for immunotherapy response and prognosis of ESCC.c